Comparison of gefitinib plus chemotherapy versus gefitinib alone for advanced non‑small‑cell lung cancer: A meta analysis (Clinics, 2023)
This study aimed to perform a meta‑analysis comparing the efficacy and safety of gefitinib in combination with chemotherapy versus gefitinib alone in patients with advanced Non‑Small Cell Lung Cancer (NSCLC). We searched databases for clinical studies that reported the efficacy or safety of gefitinib plus chemotherapy in comparison with gefitinib alone. Raw data from included studies were extracted and pooled to calculate the Odds Ratio (OR) for Objective Response Rate (ORR) and Disease Control Rate (DCR), the Hazard Ratio (HR) for Progression-Free Survival (PFS) and Overall Survival (OS), and OR for complication ≥ Grade 3. A total of 10 studies containing 1,528 patients with NSCLC were identified and included in the analysis. Gefitinib plus chemotherapy showed significantly better efficacy in improving ORR (OR = 1.54; 95% CI [Confidence Interval], 1.13‒2.1; p = 0.006), DCR (OR = 1.62; 95% CI 1.14‒2.29; p = 0.007), PFS (HR=1.67; 95% CI 1.45‒1.94; p < 0.001) and OS (HR = 1.49; 95% CI 1.2‒1.87; p < 0.001) as compared with gefitinib alone. Consistent results were observed in the sub-population with positive EGFR mutation. The combination of gefitinib with chemotherapy had a significantly higher risk of complication (≥ Grade 3) with an OR of 3.29 (95% CI 2.57‒4.21; p < 0.001). The findings in the present study suggest that the combination of gefitinib with chemotherapy can provide better disease response and survival outcomes for patients with advanced NSCLC.